THE EFFECTS OF AUTONOMY ON JOB SATISFACTION AND JOB PERFORMANCE: EVIDENCE FROM BOSNIA AND HERZEGOVINA - Nermina Delic; Irfan Djedovic; Ensar Mekic (Human Research in Rehabilitation, 2021)
The main aim of the study was to empirically investigate and understand the effects that autonomy has on job satisfaction and job performance in Bosnia and Herzegovina. The empirical data was obtained from a questionnaire of 242 people living and working in Bosnia and Herzegovina. Once the data was collected, data analysis was conducted to assure validity and reliability through items’ loadings and Cronbach’s Alpha values.Furthermore, the scales were tested for convergent validity through partial least-square path modelling using SmartPLS 3 software. The results indicated that the effects of autonomy on job performance and job satisfaction were significant and had positive relationship.